Cryoglobulinemic vasculitis with primary Sjögren's syndrome: A case report. Issue 3 (4th May 2018) - Hasegawa, Jumpei; Hayami, Noriko; Hoshino, Junichi; Suwabe, Tatsuya; Sumida, Keiichi; Mise, Koki; Ueno, Toshiharu; Yamanouchi, Masayuki; Sawa, Naoki; Ohashi, Kenichi; Fujii, Takeshi; Takaichi, Kenmei; et al.
Abstract: A 63-year-old Japanese woman with Sjögren's syndrome and peripheral neuropathy was admitted for evaluation of purpura on her lower extremities. Skin biopsy revealed leukocytoclastic vasculitis with the deposition of IgM, and serum cryoglobulin was positive. Accordingly, cryoglobulinemic vasculitis was diagnosed. There was no response to high-dose steroid therapy and plasmapheresis, but intravenous cyclophosphamide pulse therapy was effective for 4 years. Thereafter, proteinuria and hematuria developed, with cryoglobulinemic glomerulopathy being diagnosed by renal biopsy. Because the total dose of cyclophosphamide had reached 8000 mg, treatment with rituximab was selected. While rituximab was initially effective for her skin lesions and nephropathy, relapse occurred within 2 years and additional administration of this agent was required. The long-term efficacy of treatment for cryoglobulinemic vasculitis remains uncertain in patients with Sjögren's syndrome.